Monitoring of conductive hearing loss due to because of eustachian tube dysfunction preservative treated with the Otovent pneumotherapy method. - Nowak, Małgorzata; Wolnowska, Beata; Sekula, Alicja (Journal of Medical Science, 2018)
Introduction. A conductive hearing loss is a very common problem in childhood. It is possible to indicate many reasons for the problem, but most of the times it is caused by the infectious process, as well as the typical adenoid hypertrophy in children. Very often this disease is associated with obstruction of the eustachian tube. Aim. In this study, the authors present the results of the hearing tests of patients who underwent the treatment of the eustachian tube obstruction by pneumotherapy with otovent. The aim of the work was to monitor the effectiveness of this method of OME treatment. Material and Methods. The research group consisted of 54 children aged 4 to 15 years, including 23 girls and 31 boys. The control group consisted of 16 children. Pure tone audiometry and impedance audiometry were performed before and after the therapy, for all of the participants. Results. Obtained results of the study showed improvement in hearing in children correctly using the Otovent set. Hearing improvement was recorded both in the results of pure tone audiometry and impedance audiometry. Conclusions. The obtained results showed the effectiveness of the pneumotherapy method. In the case of the research group, 81.4% of children achieved the auditory norm (44 people). In the case of the control group, after a fixed period of application of the Otovent set, this value was 0%. The intergroup comparative analysis clearly shows that the research group obtained significantly better results within all of the parameters assessed, than the control group.
Keywords: conductive loss; exudative otitis media; OME; pneumotherapy; obstruction of the eustachian tube